Effects of radiation on radial growth of Scots pine in areas highly affected by the Chernobyl accident. (October 2020) - Holiaka, D.; Fesenko, S.; Kashparov, V.; Protsak, V.; Levchuk, S.; Holiaka, M.
Abstract: The effects of radiation on radial growth of Scots pine ( Pinus sylvestri s L.) affected by the Chernobyl accident were studied at five sites with different deposition levels. The study sites were chosen along a high gradient of depositions at the distance of a few hundred meters in the forests with similar forest characteristics. Air dose rates varied at the sites from the background values up to 30 μGy h −1 as of December 1, 2016. Scots pine trees exposed to sub-lethal doses of 8.6–13.2 Gy at the "Red Forest" site did not demonstrate deviations in formation of annual rings 30 years after the Chernobyl accident compared to trees with lower doses and control trees. Variation with time in annual rings thickness did reveal that the effect of radiation in trees growing at the sites with different contamination not detectable in 1986 and 1987. Conversely, the effects were clear observed in a later period in 1989–1991, i.e. 3–5 years after the accident. Until 2000, there were statistically significant differences in the annual rings growth rates of Scots pine trees exposed to external absorbed dose rates of 4.4–6.7 mGy h −1 as estimated for June 1, 1986 (or 19.5–30.0 μGy h −1 as of December 1, 2016) compared with the trees of the other sites studied. The results comply with the conclusions from research with acute pine exposure conducted in the Kyshtym area in 1975–1984. Highlights: Effects on radial growth of highly exposed trees were observed 3–5 years after the accident. The survived pine forest was recovered 30 years after the Chernobyl accident. Data on growth of annual tree rings can be used as an integral indicator of the tree exposure. Effects of annual rings tree growth comply with those observed in the Kyshtym experiments.